Does uncertainty spread vertically? A theory of multilayer newsvendors under asymmetric information. (1st November 2019) - Yang, Jiameng; Liu, Zhiyong (John); Lamb, Steven W.
Abstract: Using a vertically related multilayer newsvendors framework, this paper analyzes the impacts of market uncertainties and asymmetric information between firms at successive stages of a supply chain on their optimal stocking (and/or pricing) decisions. The asymmetric information along the supply chain effectively transmits the downstream uncertainty backward to the preceding stages of the supply chain. Our results imply that for industries in which there are lead times and asymmetric information in multiple successive stages along the supply chain, it is essentially important for the upstream firms to study the market conditions facing the vertically related downstream firms, and it is important for them to design incentive‐compatible mechanisms to facilitate efficient information sharing among vertically related entities. In these industries, the entities might also have stronger incentives to invest in lead time reduction and in information acquisition, if such options exist. Our framework offers a good starting point for a more comprehensive study in the future on the interactions among and the impact of differential lead times across successive stages in supply chains.